2016
DOI: 10.4137/jmecd.s18932
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Novel Cardiac Limited Ultrasound Exam Curriculum for Internal Medical Residency: Four Unanticipated Tasks

Abstract: Over the past two decades, our internal medicine residency has created a unique postgraduate education in internal medicine by incorporating a formal curriculum in point-of-care cardiac ultrasound as a mandatory component. The details regarding content and implementation were critical to the initial and subsequent success of this novel program. In this paper, we discuss the evidence-based advances, considerations, and pitfalls that we have encountered in the program's development through the discussion of four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Few studies have examined residents’ skills and attitude towards POCUS training,2838 but to the best of our knowledge, no prior study has compared POCUS image interpretation skills and self-reported confidence between residents with and without POCUS training in medical school. The goal of this study was to assess our residents’ attitude, basic needs, and prior knowledge about POCUS and whether POCUS training and exposure during medical school influences their POCUS image interpretation skills and confidence level.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined residents’ skills and attitude towards POCUS training,2838 but to the best of our knowledge, no prior study has compared POCUS image interpretation skills and self-reported confidence between residents with and without POCUS training in medical school. The goal of this study was to assess our residents’ attitude, basic needs, and prior knowledge about POCUS and whether POCUS training and exposure during medical school influences their POCUS image interpretation skills and confidence level.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Society of Hospital Medicine is actively releasing position statements on certification in point‐of‐care ultrasonography and creating a certification program (https://www.hospitalmedicine.org/clinical-topics/ultrasonography-cert/). In response, some internal medicine residency programs have identified the need to train their residents and hence have preemptively developed formal curricula in point‐of‐care ultrasonography . How best to instruct and how often to retrain noncardiologists in FCU remains unclear.…”
mentioning
confidence: 99%
“…In response, some internal medicine residency programs have identified the need to train their residents and hence have preemptively developed formal curricula in point-of-care ultrasonography. [3][4][5][6] How best to instruct and how often to retrain noncardiologists in FCU remains unclear.…”
mentioning
confidence: 99%
“…This study advances older and smaller observations showing the feasibility of newly trained resident physicians in internal medicine to learn and perform US examinations and demonstrates, in particular, the successful clinical use of pocket‐sized devices . The CLUE used in the study has been well established as a required curriculum of a medical residency for greater than a decade, and the residents performing POCUS examinations in this study were not hand‐selected or motivated volunteers but random senior residents demonstrating their routine behaviors while admitting patients during a required rotation. The considerable but lesser accuracy (79%) of resident examinations may be explained by the inability to obtain a single view, the interobserver variability on subjective, borderline findings, or the evanescent nature of some initial CLUE findings, such as lung B‐lines and IVC plethora, which may have been altered by treatments in the emergency department and later absent during reference standard imaging.…”
Section: Discussionmentioning
confidence: 77%
“…This study was conducted at a 300‐bed community teaching hospital in which all 36 residents in the 3‐year internal medicine residency program were trained in CLUE and had been routinely scheduled for a “night float” rotation in their second or third year. In the 2‐week rotation, the resident independently admitted up to 6 patients to the ward and intermediate‐care units primarily from the emergency department and subsequently signed over patient care to a medical team in the morning, henceforth having no further coverage or effect on the management, treatment, or discharge of the patient.…”
Section: Methodsmentioning
confidence: 99%